Nanomaterials in Industry: A Review of Emerging Applications and Development - Kumar, Swarup; Khan, Saidul Islam; Neidhe, Md Musfiqur Rahman; Islam, Monirul; Hasan, Md Mehedi (Control Systems and Optimization Letters, 2024)
Nanomaterials are materials where at least one dimension is smaller than 100 nanometers, unlocking a realm of extraordinary properties that set them apart from their bulk counterparts. These materials exhibit unique behaviors, such as enhanced electrical conductivity, superior mechanical strength, and heightened chemical reactivity. Due to these qualities, they are widely used in sectors like as electronics, healthcare, energy, and environmental preservation. Nanomaterials have made it possible for electronics to get smaller, and they have enhanced medication delivery and diagnostics in the medical field. They are perfect for energy conversion and storage technologies like solar cells and batteries because of their large surface area and conductivity. Furthermore, the use of nanoparticles in sustainable agriculture and environmental remediation is being investigated. Nevertheless, there are still difficulties in meeting regulatory requirements, guaranteeing safety, and increasing output. This paper looks at the many uses for nanomaterials, emphasizes their promise, and discusses the obstacles preventing a wider industrial acceptance of them.